Laparoscopic ureteroureterostomy for benign non-passable upper ureteric stricture – A case report with review of literature - Agrawal, Prachi Praveen; Shetty, Prakash Chandra; Joshi, Abhijit S (Indian Journal of Case Reports, 2024)
Ureteral stricture (US) is not a very common condition. The etiology of US could be either benign or malignant. It is mostly due to long-standing ischemia causing inflammation and fibrosis that ultimately leads to stricture formation. In most cases, diagnosis is made incidentally under direct visualization at the time of the ureteroscopic procedure. Surgery for ureteral reconstruction aims to achieve adequate vascular supply, a tension-free anastomosis with mucosal apposition, and to ensure complete excision of stricture-laden ureteral segments. We herein present the case of a 42-year-old male patient who presented with a complaint of acute pain in his left flank, radiating from the loin to the front, for 10 days. The workup investigations revealed a tight stricture in the left upper ureter, a 2-mm calculus in the left upper ureter proximal to the stricture, and left proximal hydroureteronephrosis. The patient was successfully managed by laparoscopic ureteroureterostomy.